Собрание соч.: в 8 т. (Ж. Верн ; сост. Н. Н. Жегалов) - Верн Жюль (1985)
Экземпляры: ф.4 (1985) / Инвентарный номер: 10514 / Цена: 2.60 / Сис.шифр: 84(4Фра) / Авт.знак: В 35 / ГРНТИ: 17.82 / ББК: 84(4Фра)